Pendekatan Diagnosis pada Sindrom Sezary - Fitri Nadia Silvani (MAJORITY, 2020)
Sezary syndrome is a rare, aggressive leukemia variant of Cutaneous T-Cell Lymphoma (CTCL) that performs clonal proliferation of malignant T lymphocytes with a predisposition to cutaneous erythroderma. The incidence of CTCL in the United States during 2000-2010 reached 10 cases per one million people per year. Sezary syndrome is a rare form of CTCL, accounting for 3% of all cutaneous lymphomas. In Indonesia, lymphoma together with Hodgkin's lymphoma and leukemia ranks the 6th malignancy. Besides Sezary syndrome being a rare case, Sezary syndrome is an aggressive case so it has a poor prognosis with an average survival of 5 years. The aim of this literature review is to increase knowledge in constructing the prompt diagnosis of Sezary's syndrome based on subjective and objective findings. In conclusion, the diagnosis of Sezary syndrome can be made immediately on subjective and objective grounds, known as the Sezary syndrome triad, that are 1) generalized exfoliative dermatitis (affecting> 80% of body surface area), 2) lymphadenopathy, and 3) the presence of 5% or more malignant T cells with a cerebriform nucleus (known as Sezary or Lutzner cells) in peripheral blood lymphocytes.